A 100 μm diameter capacitive pressure sensor with 50 MPa dynamic range. (7th March 2016) - Luo, Xin; Gianchandani, Yogesh B
Abstract: This paper presents fully sealed absolute capacitive pressure sensors for high-pressure applications in hydraulic environments. The sensors have a ø100 μ m diaphragm and a nominal interelectrode gap of 3 μ m. The interiors of the cavities are electrically isolated, allowing the sensors to operate at the high end of the pressure range with the center of the diaphragm in contact with the substrate beneath it. The sensors are monolithically fabricated using a combination of surface micromachining and through-wafer isolated bulk-silicon lead transfer for backside contacts. This structure allows the device footprints to be reduced to about 150 × 150 μ m 2, and simplifies system integration. Fabricated sensors with diaphragm thicknesses of 3 μ m (C100t3) and 5 μ m (C100t5) are tested in an oil environment at pressures up to 20 MPa and 50 MPa, respectively. The average sensitivities are 7200 ppm MPa −1 (3.1 fF MPa −1 ) for C100t3, and 3400 ppm MPa −1 (1.6 fF MPa −1 ) for C100t5 in the non-contact mode. In the contact mode, the average sensitivities are 9900 ppm MPa −1 (5.3 fF MPa −1 ) for C100t3, and 3100 ppm MPa −1 (1.6 fF MPa −1 ) for C100t5. A multiphysics finite element analysis approach that accommodates contact mode simulations is also presented.